2017
DOI: 10.5539/ijbm.v12n12p64
|View full text |Cite
|
Sign up to set email alerts
|

The Market Reaction to the Appointment of Women on Corporate Boards: Evidence from the Italian Listed Companies

Abstract: During the 2012-2016 period, a large number of Italian companies appointed women directors in their boards, an unusual and unpredictable fact in the Italian industrial system. This paper investigates if any significant reaction has consequently occurred in the Italian stock market. It assumes that a significant market reaction would indicate the investors view the female board members as a strategic value added at the decision making level. To achieve the objective, it was collected a database consisting of 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…In a nutshell, as confirmed in earlier studies (Pastore and Tommaso, 2016;di Donato et al, 2016;Pastore et al, 2017;Solimene et al, 2017), the implementation of Law 120/2011 launched a significant upward trend by increasing both the number of women sitting in the Italian corporate boards and the number of companies in which both genders are represented. However, the progress made by women mainly referred to non-executive positions and they keep managing as non-executive and independent members.…”
Section: A Literature Review On Gender Diversity and Quotasmentioning
confidence: 59%
“…In a nutshell, as confirmed in earlier studies (Pastore and Tommaso, 2016;di Donato et al, 2016;Pastore et al, 2017;Solimene et al, 2017), the implementation of Law 120/2011 launched a significant upward trend by increasing both the number of women sitting in the Italian corporate boards and the number of companies in which both genders are represented. However, the progress made by women mainly referred to non-executive positions and they keep managing as non-executive and independent members.…”
Section: A Literature Review On Gender Diversity and Quotasmentioning
confidence: 59%
“…Specifically, by appointing a woman as a board member, firms signal their commitments to mitigate the possibility of risk-related issues, such as earning management and tax avoidance, destroy their reputation. Although a study documents that market does not react strongly enough to the announcement of the appointment of women in top management teams (Pastore et al , 2017), other studies show that the appointment of female directors is likely to add value, and stock markets react positively to such announcements (Campbell and Vera, 2010; Kang et al , 2010; Sudeck and Iatridis, 2014).…”
Section: Background Literature and Hypotheses Developmentmentioning
confidence: 99%
“…The announcements of top executive appointments, particularly those of CEOs, have significantly impacted investors' evaluation of firms (Gangloff, Connelly, & Shook, 2016). Studies have shown that investors react to these appointments either positively or negatively, depending on specific characteristics of the newly appointed CEOs (Pastore, Tommaso, & Ricciardi, 2017; Rose, 2019). Several studies found evidence that investors react more negatively to a minority‐status CEO's appointments, such as female CEOs (Gaughan & Smith, 2016; Lee & James, 2007).…”
Section: Introductionmentioning
confidence: 99%